2021
DOI: 10.1098/rsbl.2021.0222
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional ancient DNA preservation and fibre remains of a Sasanian saltmine sheep mummy in Chehrābād, Iran

Abstract: Mummified remains have long attracted interest as a potential source of ancient DNA. However, mummification is a rare process that requires an anhydrous environment to rapidly dehydrate and preserve tissue before complete decomposition occurs. We present the whole-genome sequences (3.94 X) of an approximately 1600-year-old naturally mummified sheep recovered from Chehrābād, a salt mine in northwestern Iran. Comparative analyses of published ancient sequences revealed the remarkable DNA integrity of this mummy.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…DNA of the mummified baboon shows postmortem damage, which is, however, relatively low compared to what can be expected for samples of similar age (Dabney, Meyer, et al, 2013, Kistler et al, 2017). Low frequencies of post mortem damage were observed for aDNA from mummified specimens and have been attributed to the water deprivation during the mummification process, which may prevent hydrolytic deamination (Rossi et al, 2021). Postmortem damage observed here is within the range previously reported for aDNA derived from Egyptian human mummies (Schuenemann et al, 2017) and a Iranian saltmine sheep mummy (Rossi et al, 2021), which supports the authentic origin of our ancient sequence data and tends to rule out the possibility of contamination with modern DNA.…”
Section: Discussionmentioning
confidence: 99%
“…DNA of the mummified baboon shows postmortem damage, which is, however, relatively low compared to what can be expected for samples of similar age (Dabney, Meyer, et al, 2013, Kistler et al, 2017). Low frequencies of post mortem damage were observed for aDNA from mummified specimens and have been attributed to the water deprivation during the mummification process, which may prevent hydrolytic deamination (Rossi et al, 2021). Postmortem damage observed here is within the range previously reported for aDNA derived from Egyptian human mummies (Schuenemann et al, 2017) and a Iranian saltmine sheep mummy (Rossi et al, 2021), which supports the authentic origin of our ancient sequence data and tends to rule out the possibility of contamination with modern DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when genotyping the hairy/woolly locus in a ~ 1600-year-old naturally mummified sheep found in a salt mine ( Chehrābād ) in northwestern Iran, the ancestral “hairy” allele (likely IRF2BP2 wt/wt or IRF2BP2 wt/asEIF2S2 ) was identified [ 152 ]. In addition, using scanning electron microscopic observations of the mummified hair fibers showed characteristics that are specific to sheep hair fibers of mouflon and medium-wool breeds.…”
Section: Main Textmentioning
confidence: 99%
“…In addition, using scanning electron microscopic observations of the mummified hair fibers showed characteristics that are specific to sheep hair fibers of mouflon and medium-wool breeds. This suggested that, during that ancient period, the herd was maintained for meat or milk production rather than wool extraction, and ovicaprids were destined to be used as food source for workers in that location [ 152 ]. This study highlighted the potentiality of using a locus for the phenotypic characterization of ancestral breeds using ancient DNA.…”
Section: Main Textmentioning
confidence: 99%
“…A ca. 1600-year-old sheep mummy from a Sasanian salt mine in Chehrābād, Iran, was shown to be of the 'hairy' type by genetic and morphological analysis of exceptionally preserved mummified fiber remains [211]. This suggests that woolly sheep did not become a universal norm even in 1st millennium CE Southwest Asia, and that hairy breeds may have been used at this time for specialized milk and meat production.…”
Section: Wool Growthmentioning
confidence: 99%